One version of the projection-iterative method based on the method of chords - Galushko, N. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider the problem of application of one version of the projection-iterative method to nonlinear integral equations. Sufficient conditions for the convergence of this method are established.